Analisis Ketimpangan Ekonomi Antarwilayah di Provinsi Jawa Tengah Sebelum Omnibus Law Cipta Kerja - Mahardhika Cipta Raharja; Unik Lestari (OECONOMICUS Journal of Economics, 2022)
This study analyzes the effect of Foreign Investment (PMA), Domestic Investment (PMDN), and the Human Development Index on the inequality of district/city development and how the mediating variable of the Human Development Index (IPM) also affects the inequality of district/city development in Central Java Province, before the Omnibus Law Cipta Kerja. Data analysis uses path analysis with the Eviews program, using data from 35 districts/cities in Central Java Province in the 2016-2019 period. The result is that PMDN and PMA have a positive effect on IPM. PMDN and IPM have a negative effect on development inequality, while PMA has no effect on district/city development inequality in Central Java Province.